1992
DOI: 10.1080/15287399209531676
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression by chronic exposure toN‐nitrosodimethylamine (NDMA) in mice

Abstract: Immunosuppression of humoral and cellular responses following chronic oral exposure to 1, 5, 10, and 20 ppm N-nitrosodimethylamine (NDMA) was examined in CD-1 mice. Monitoring of cumulative mortality and the incidence of peritoneal ascites in animals showed an NDMA dose-related mortality and hepatotoxicity. No visible changes in immunological parameters were noted at the 1 ppm NDMA dose. Immunosuppression of immunoglobulin M (IgM) antibody response by NDMA to sheep red blood cells (SRBC) was time-related, dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Our ndings agree with those of Stahlman (1992) who found a dose-dependent decrease in IgG in rats after acyclovir exposure and with Banerjee et al (1996) who found that aldrin and DDT suppress both IgG and IgM levels to the pesticide-exposed rats. However, our ndings contrast with Fournier et al (1992) and Desjardins et al (1992) who reported suppression of primary humoral response N-nitrosodimethylamine and atrazine treatment.…”
Section: Discussioncontrasting
confidence: 85%
“…Our ndings agree with those of Stahlman (1992) who found a dose-dependent decrease in IgG in rats after acyclovir exposure and with Banerjee et al (1996) who found that aldrin and DDT suppress both IgG and IgM levels to the pesticide-exposed rats. However, our ndings contrast with Fournier et al (1992) and Desjardins et al (1992) who reported suppression of primary humoral response N-nitrosodimethylamine and atrazine treatment.…”
Section: Discussioncontrasting
confidence: 85%
“…Carcinogenic compounds can cause irritation and inflammation at sites of exposure and are often antigenic (251)(252)(253)(254)(255)(256)(257)(258)(259). Respiratory carcinogens (or suspected carcinogens) include antimony compounds (260)(261)(262)(263), arsenic compounds (263)(264)(265)(266)(267)(268), hexamethylphosphoramide (269,270), 4,4´-methylene-bis(2-chloroaniline) (271,272), bromoform (273,274), methylene chloride (275), 4,4´-methylenedianiline (276,277), nitrobenzene (mice) (278-280), 4-nitrobiphenyl (281), 2-nitropropane (282)(283)(284)(285), N-nitroso-Nmethylurea (286), N-nitrosodimethylamine (287)(288)(289)(290), N-nitrosomorpholine (291-293), pentachlorophenol (mice) (294,295), polycyclic aromatic hydrocarbons (250,254,255), 1,3-propane sultone (296,297), propylene oxide (298-300), 2,3,7,8-tetrachlorodibenzop-dioxin (TCDD) (301-305), 2,4-toluene diamine (306,307), viny...…”
Section: Evaluating Human Exposure and Its Relationship To Asthmamentioning
confidence: 99%
“…[7] and Desjardins et a/. [8] who reported suppression in only the primary humoral response with N-nitrosodimethylamine and atrazine treatment. In the present study, Neemazal did not suppress the primary or secondary antibody response.…”
mentioning
confidence: 95%